1998
DOI: 10.1093/humrep/13.10.2748
|View full text |Cite
|
Sign up to set email alerts
|

One year of experience working with the aid of a robotic assistant (the voice-controlled optic holder AESOP) in gynaecological endoscopic surgery

Abstract: The aim of the study was a comparison of robotic versus human laparoscopic camera control. Utilizing robotic technology a robot has been designed specifically for the purpose of holding and manoeuvring the laparoscope under the direct control of the surgeon. We tested AESOP (automated endoscopic system for optimal positioning) in 50 patients undergoing routine gynaecological endoscopic surgical procedures. The elimination of the camera holder allows two doctors to perform complex laparoscopic surgery faster th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(65 citation statements)
references
References 1 publication
0
56
0
5
Order By: Relevance
“…Surgeons in Kiel, Germany, explored the use of AESOP in gynecological laparoscopic operations and compared voice control of AESOP with the older foot or hand control systems [27]. They found that the robotic arm allowed them to perform complex laparoscopic operations faster than when the camera was held by a human assistant.…”
Section: Aesopmentioning
confidence: 99%
“…Surgeons in Kiel, Germany, explored the use of AESOP in gynecological laparoscopic operations and compared voice control of AESOP with the older foot or hand control systems [27]. They found that the robotic arm allowed them to perform complex laparoscopic operations faster than when the camera was held by a human assistant.…”
Section: Aesopmentioning
confidence: 99%
“…The irst FDA-approved surgical robot, the automated endoscopic system for optimal positioning (AESOP, Computer Motion Inc.), was a teleoperated robotic endoscopic camera that followed the commands of the surgeon via either pedals or voices. The AESOP system was successfully used in laparoscopic surgical procedures in areas such as urology, gynecology, etc., [4][5][6][7]. The subsequent ZEUS robotic system (Computer Motion Inc.) complemented an AESOP camera with two teleoperated robotic manipulators that were also continuously controlled by the surgeon through motion or voice commands [1,8].…”
Section: Surgical Robots Todaymentioning
confidence: 99%
“…The technology is, however, very expensive and the overall benefit is still under evaluation [26]. Simpler automated control devices for the laparoscope and camera have been developed including voice activated camera control, AESOP [27]. They may have a place, particularly in the era of fewer surgical assistants.…”
Section: Introductionmentioning
confidence: 99%